High prevalence of multiple antibiotic resistance in fermented food-associated lactic acid bacteria in Malaysia - Haryani, Yuli; Abdul Halid, Nadrah; Goh, Sur Guat; Mahmud Ab Rashid, Nor-Khaizura; Md Hatta, Muhammad Asyraf; Sabri, Suriana; Radu, Son; Hasan, Hanan (Elsevier, 2022)
Fermented foods may serve as a vector for introducing non-pathogenic antibiotic-resistant bacteria into the human gastrointestinal system, thereby interacting with the gut microbiota, and disseminating antibiotic-resistant genes. The present work thus aimed to investigate the genetic diversity, antibiotic resistance, and plasmid profiles of lactic acid bacteria (LAB) isolated from selected homemade and manufactured fermented foods and beverages in Malaysia. Random amplified polymorphic DNA (RAPD) typing showed high reproducibility with satisfactory discriminatory power of 0.88, assigning 55 LAB isolates to 54 strains. Antibiotic susceptibility against 13 antibiotics was analysed using the disc diffusion method. Multidrug resistance (MDR) was detected on 51 of 55 isolates with a high occurrence of β-lactam/cephalosporin and aminoglycoside resistance. Multiple antibiotic resistance (MAR) index in 48 isolates exceeded the high-risk level (0.2). The average plasmid size of 7 kb was detected in 32 out of 40 plasmid-harbouring isolates; however, no direct correlation between the presence of plasmids and resistance patterns was observed. The high number of MDR strains and MAR index demonstrated increasing antibiotic resistance in LAB which could pose a serious threat to human health, thus signifying the need to monitor the antibiotic resistance pattern of LAB in the fermented food industries.